APLIKASI SISTEM KEUANGAN MUSYARAKAH MUTANAQISHAH SEBAGAI INSTRUMEN PERMODALAN UMKM DI INDONESIA - Muflih, Muhammad; Setyowati, Diharpi Herli (El-Qist: Journal of Islamic Economics and Business (JIEB), 2015)
This study is intended to give the solution of minimum rate of funding in the area of small and middle enterprise. So far, Islamic banking posses the system of musyaraqah mutanaqishah (MMQ) as the new way in enlarging the scope of business of profit sharing system. Unfortunately, in the real process, this system was intent on optimalizing the property business. This study tries creating the new direction of MMQ, namely to organize the potentiality of MMQ in lifting up its funding system for the existance as well as the sustainability of small and middle enterprise. By applied analysis approach, this study was successful in configurating the practice system of MMQ funding in the region of small and middle enterprise. To make easy the process of application, baitul mal wa tamwil is laid as the experiment place.